A study on the relationship between money supply (M3), gross national product (GNP), treasury bills (T-Bills), and consumer price index (CPI) towards Kuala Lumpur Composite Index (KLCI) / Azwardi Che Ab. Ghani - Che Ab. Ghani, Azwardi (2005)
The study concentrates on the relationship between the money supply (M3) gross national product (GNP), Treasury bills (T-Bills) and consumer price index (CPI) towards Kuala Lumpur Composite Index (KLCI). The purpose of the study is to identify whether the money supply (M3). gross national product (GNP) Treasury Bills (T-bills)., and consumer price index (CPI) has positive or negative relationship with Kuala Lumpur Composite Index (KLCI). The fluctuation of KLCI from 1994 to 2004 which is patents its instability, which something too high and something too low The composite index instability and uncertainty pose significant challenge to the policy makers and investors in coming up with investment plan to minimize risk. The researcher use these independent variable because based on the previous study, the macroeconomic variables such as money supply, lending rate, inflation rate, discount rate, and gross national product influence to the KLCI. The secondary data is collected on monthly basis taken from 1 January 1994 to 31 December 2004. This study is use Multiple Regression Model to analyze the four variables concerned. From the result, it is shown that money supply (M3) and gross national product (GNP) has significant relationship with Kuala Lumpur Composite Index (KLCI). Then, the Treasury Bills (T-Bills) and consumer price index (CPI) has no significant relationship with Kuala Lumpur Composite Index (KLCI).